JURNAL PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK ENERVON-C - Charlie Bernando Halomoan Samosir; Arief Bowo Prayoga (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
Level of competition companies that sell adult multivitamin product is getting tougher due to the increasing demand of multi-vitamins, especially vitamin C. People are faced with a wide selection of products, so that the perception of price and promotional activities are carried into consideration in product purchasing decisions. This study aimed to test whether the effect of the perception of price and product promotion Enervon-C on product purchasing decisions. This study was conducted on 100 people Enervon-C product buyers in supermarkets Tip Top Ciputat,Tangerang Banten with convinance sampling method. The empirical test results indicate that the perception of price and promotion has a positive and significant influence on purchasing decisions product of Enervon-C, nevertheless contributes only 50.2% to the purchasing decision.Keywords: Perception Price, Promotion, Consumer Purchasing Decision, Product Enervon-C.